EFFECT OF PARTIALLY ACIDULATED ROCK PHOSPHATE ON GROWTH AND YIELD OF MAIZE IN A CALCAREOUS SOIL COMPARED WITH SOME TRADITIONAL PHOSPHATE FERTILIZERS - & Al-Hadethi, Al-Kubissi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Two experiments were conducted to study the impact of adding partial acidulated rock phosphate in comparison with traditional phosphate fertilizers. First experiment was conducted to study Kinetics of P release from partially acidulated pock phosphate (30, 40, 50, 60, and 70%) or from TSP and SSP at 80 kg P ha-1. The results showed that the release of phosphorous from acidified rock phosphate was characterized by 1st order kinetics with high (R2) and lowest SEe. TSP gave the highest quantity of soluble phosphate in aliquot compared to SSP. The 2nd experiment was a field one aimed to study the effect of partial acidulated rock phosphate on growth and yield of maize compared in comparison to TSP and SSP. The results showed that partially acidulated RP at 70% level was superior for all parameters of growth and yield of maize over all other treatments. The 70% partially acidulated gave the highest, plant dry matter, seed weight for individual plant, total plant seed yield, which was in value of, 332.20 gm.plant-1, 181.5 gm.plant-1 and 13.625 Mg.ha-1 respectively, but with no significant differences than 60%.therfore , 60% acidulation can be recommended under used management practices.